The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s12274-022-5275-5
|View full text |Cite
|
Sign up to set email alerts
|

Native and engineered exosomes for inflammatory disease

Abstract: Exosomes are extracellular vesicles which carry specific molecular information from donor cells and act as an intercellular communication vehicle, which have emerged as a novel cell-free strategy for the treatment of many diseases including inflammatory disease. Recently, rising studies have developed exosome-based strategies for novel inflammation therapy due to their biocompatibility and bioactivity. Researchers not only use native exosomes as therapeutic agents for inflammation, but also strive to make up f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 179 publications
0
17
0
Order By: Relevance
“…Similar to the cells, the mechanisms responsible for the therapeutic effects of the EVs in the context of different inflammatory diseases are reducing the microglia/macrophage activation, oxidative stress, pro-inflammatory cytokine and chemokine release, T-cell activation, tissue fibrosis, viral infectivity, immune cell infiltration, and apoptosis/necrosis ( 146 ). Moreover, EVs regulate M1/M2 macrophage polarization for the benefit of M2 cells, induce collagen regeneration, and prevent scar generation ( 181 ).…”
Section: Msc-evs Vs Mscs: Open Issuesmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar to the cells, the mechanisms responsible for the therapeutic effects of the EVs in the context of different inflammatory diseases are reducing the microglia/macrophage activation, oxidative stress, pro-inflammatory cytokine and chemokine release, T-cell activation, tissue fibrosis, viral infectivity, immune cell infiltration, and apoptosis/necrosis ( 146 ). Moreover, EVs regulate M1/M2 macrophage polarization for the benefit of M2 cells, induce collagen regeneration, and prevent scar generation ( 181 ).…”
Section: Msc-evs Vs Mscs: Open Issuesmentioning
confidence: 99%
“…Having mentioned these differences, EVs generally have some clinically relevant superiorities to cell therapy ( 185 , 264 , 265 ). The immune rejection rate of EVs is considerably low compared to the producer cells ( 181 ), so they have an increased half-life and are more stable in circulation ( 39 ). EVs demonstrate an innate tropism to specific tissues ( 76 ) and exert cell-targeting properties ( 111 ).…”
Section: Msc-evs Vs Mscs: Open Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that exosomes are closely related to the development of diseases. [64,65] The main method of detecting exosomes reported now is fluorescence detection, however, the strong autofluorescence signals in the plasma and the culture medium (mostly emit from the emissive biomolecules, such as hemoglobin, flavin, and lipofuscin) can interfere the measurements, during fluorescence detection. To avoid this [51] Copyright (2020), The Author(s).…”
Section: Detection Of Exosomesmentioning
confidence: 99%